Development of a Soil Moisture Control System with PC Monitoring - Daffallah, Khalid O.; Abdellattif, Gaafer M.; Adam, Adam I. (Gezira Journal of Engineering and Applied Sciences, 2010)
} PC   Moisture Sensor   The purpose of this study is to develop an irrigation system flow control valve consisting of conjunction channels through a personal computer (PC) batch to monitor the water flow into a specific area of soil when it reaches a lowest moisture level (threshold), i.e. somewhat dry. When the soil moisture reaches the threshold of specific moisture content, the control valve opens for a specified period of time to moisten that spot of soil. When the moisture content reaches the threshold, the valve is closed. The valve control was fitted to the outlet of the water tank. The valve electric supply was controlled by the sensor monitor system so that water was flowing through it and reaches into the soil. When the electricity was cut from the valve, this closed the valve and stopped pumping water to the soil. A computer program was developed to monitor the soil moisture sensor and the water valve.